Catalytic degradation of polystyrene - Rapid Communication - Kijeński, J.; Kaczorek, T. (Polimery, 2022)
Syndiotactic polystyrene was degraded in an atmosphere of N2 or H2 at 375 or 400 degrees C in the presence of transition metal catalysts (Cr, Ni, Mo, Co or Fe) on the support (Al2O3, SiO2). Styrene, ethyl benzene, a-methylstyrene, cumene, toluene, benzene as well as bi- and tricyclic hydrocarbons were found in the reaction products. Effects of degradation conditions on the products compositions were discussed. The highest yield of styrene monomer (>80 %) was reached when iron-based catalysts were used.